Chemical constituents from the leaves of Cinnamomum parthenoxylon (Jack) Meisn. (Lauraceae). (February 2017) - Wei, Xuan; Li, Guo-Hui; Wang, Xiao-Ling; He, Ji-Xiang; Wang, Xiao-Ning; Ren, Dong-Mei; Lou, Hong-Xiang; Shen, Tao
Abstract: Phytochemical investigation of the ethanolic extract from the leaves of Cinnamomum parthenoxylon (Jack) Meisn. led to the isolation of (3 R, 4 R, 3′ R, 4′ R )-6, 6′-dimethoxy-3, 4, 3′, 4′-tetrahydro-2H, 2′H-[3, 3′]bichromenyl-4, 4′-diol (1 ), 4-hydroxybenzaldehyde (2 ), 1, 2, 4-trihydroxybenzene (3 ), kaempferol-3- O -α-l -rhamnoside (4 ), herbacetin (5 ), quercetin-3- O -α-l -rhamnoside (6 ), daucosterol (7 ), and β-sitosterol (8 ). The structures were established by extensive analysis of their MS and NMR spectroscopic data and comparison with literature data. In the present research, all of the isolated compounds1 –8 are reported for the first time in the species C. parthenoxylon . Compounds1 –6 were firstly isolated from genus Cinnamomum . Compounds1, 3, 5 and6 have not been reported from any species in Lauraceae family. The chemotaxonomic significance of the isolated compounds is discussed. Highlights: One chromene dimer, two benzenoids, three flavonoids, and two steroids have been isolated from Cinnamomum parthenoxylon . Compounds1 –8 are firstly reported in the species Cinnamomum parthenoxylon. Compounds1 –6 are firstly isolated from genus Cinnamomum. Compounds1, 3, 5 and6 are firstly reported from family Lauraceae.